Influence of government policies on handwashing and vaccine uptake in Kenya, Uganda, and Tanzania to prevent and control COVID-19: a systematic review - Muchangi, Josphat Martin; Mturi, James; Mukasa, Hajra; Kithuki, Kioko; Kosgei, Sarah Jebet; Kanyangi, Lennah Muhoja; Moraro, Rogers; Kamau, Samuel; Nankanja, Maureen (Frontiers in Public Health, 2024)
IntroductionThe government's role in influencing policies related to Coronavirus disease 2019 (COVID-19) vaccine distribution and handwashing practices is essential in controlling the spread of severe acute respiratory syndrome coronavirus 2.MethodsThis study aimed to systematically review published studies to explore the influence of government policies on handwashing and vaccine uptake in Kenya, Uganda and Tanzania to prevent and control COVID-19. A comprehensive search strategy was applied across three databases, and eligibility was determined using strict inclusion and exclusion criteria. We reviewed 9 of 136 research papers following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines.ResultsThe findings revealed that the government has a role in influencing policies related to COVID-19 vaccine distribution and handwashing uptake. Employment of public health campaigns and communication strategies by the government in Uganda increased vaccine acceptance and hand hygiene uptake. Similarly, government efforts to make hand hygiene accessible increased the uptake of handwashing in Tanzania. In Kenya, government efforts to increase access to soap and clean water in informal settlements and markets resulted in increased adherence to handwashing practices. Further, government incentives such as cash increased vaccination rates while vaccination reminders combined with cash incentives increased childhood immunization coverage.DiscussionOverall, this review indicates that monitoring and enforcing compliance increases vaccine and handwashing uptake across the three countries. The effectiveness of government policies on handwashing and vaccine uptake is influenced by factors such as safety, efficacy and access to information, among others. Therefore, there is a need to address these factors for the successful implementation of these policies.Systematic review RegistrationPROSPERO ID CRD42023396319, https://www.crd.york.ac.uk/prospero/.